PENGARUH VARIASI KUAT ARUS TERHADAP KEKUATAN TARIK SAMBUNGAN LAS TIG SEMI OTOMATIS - Paundra, Fajar (Politeknik Harapan Bersama Tegal, 2022)
Tungsten Inert Gas is a type of welding that uses noble gases as a shield from the influence of outside air. The purpose of this study was to determine the effect of variations in current strength on the tensile strength of semi-automatic TIG welded joints. The welding process is carried out with current variations of 70A, 80A, 90A and 10A, while the welding speed is 10 m/s. Tensile testing was carried out using the JIS Z 2201 standard. The test results showed that the highest tensile strength was found in the 100A variation of 370MPa. This happens because the results of the welding process with 100A occur slightly welding defects so that it has a high tensile strength.